1999
DOI: 10.1046/j.1365-2044.1999.01108.x
|View full text |Cite
|
Sign up to set email alerts
|

Extending low‐dose epidural analgesia for emergency Caesarean sectionA comparison of three solutions

Abstract: SummaryWe conducted a prospective double-blind randomised trial to compare bupivacaine 0.5%; a 50 : 50 mixture of bupivacaine 0.5%/lignocaine 2% with 1 : 200 000 adrenaline (final concentration); and lignocaine 2% with 1 : 200 000 adrenaline for converting a low-dose labour epidural into a block adequate for emergency Caesarean section. Ninety patients were studied, 30 in each group. There was no difference between the groups in the time taken for bilateral loss of cold sensation to reach T 4 . Onset time was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
58
4
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 13 publications
1
58
4
1
Order By: Relevance
“…12 However, in recent studies, inadequate surgical anesthesia after conversion of ELA to ESA for CD necessitated conversion to GA in 2.5-20% of cases and provision of additional analgesia was even more frequent. [13][14][15][16][17][18][19] Only one underpowered study reported a conversion rate to GA of 0%. 20 In fact, inadequate ESA has led to litigation against anesthesiologists.…”
Section: Discussionmentioning
confidence: 99%
“…12 However, in recent studies, inadequate surgical anesthesia after conversion of ELA to ESA for CD necessitated conversion to GA in 2.5-20% of cases and provision of additional analgesia was even more frequent. [13][14][15][16][17][18][19] Only one underpowered study reported a conversion rate to GA of 0%. 20 In fact, inadequate ESA has led to litigation against anesthesiologists.…”
Section: Discussionmentioning
confidence: 99%
“…These have been in varying study populations with different epidural regimens in labour, and have used different sensory modalities and end-points for surgical anaesthesia [1,2,4,5,14], making it difficult to compare studies. We attempted to define our end-points more clearly by specifying 'icy' cold sensation and 'strong' touch sensation, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…A power analysis was performed with values for alpha and beta of 0.05 and 0.2, respectively, based on a 50% relative decrease in intra-operative supplementation, and a 30% reduction in onset time, using data from previous studies [1,2]. This indicated sample sizes of 82 and 86, respectively, hence the planned sample size of 100 per group to account for drop-outs.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations